Pengaruh Promosi dan Harga Terhadap Kepuasan serta Implikasinya pada Loyalitas Pelanggan di Wedrink Daerah Jakarta - YB Andre Marvianta; Vinky Xander (Syntax Idea)
This study intends to determine the effect of promotions and prices on customer satisfaction and their implications on Wedrink customer loyalty in Jakarta. The population of this study is all customers who have visited Wedrink Jakarta. This study used descriptive analysis and Structural Equation Modeling (SEM). The techniques chosen were purposive sampling and non-probality sampling with a total of 381 respondents. The results show that Promotion has a significant effect on customer satisfaction, Price has a significant effect on customer satisfaction, Promotion has a significant effect on customer loyalty, Price has a significant effect on customer loyalty, Customer satisfaction has a significant effect on customer loyalty. It is recommended to set the appropriate price so that customers are more interested and provide many promotions to customers to build a sense of satisfaction from customers and give appreciation to customers who are already loyal and make repeat purchases.